Physicochemical, antioxidant and enzymes activities of grape fruit peel and pomace enriched functional drinks - Ali, Sidra Muhammad; Imran, Ali; Arshad, Muhammad Umair; Ahmed, Rabia Shabir; Imran, Muhammad (Cellular and Molecular Biology, 2021)
Experiment was conducted to determine the proximate, minerals, antioxidant capacities and enzymes activities of grape fruit peel and grape fruit pomace along with sensorial evaluation of functional drinks. In this milieu, values of grapefruit peel and pomace powder for moisture, fat, crude protein, carbohydrate, crude fiber, ash, and NFE were recorded as 10.85±1.34,8.9±0.08 , 9.27±0.03, 7.69±0.02, 60.22±2.32, 50.33±2.1, 6.13±0.02, 6.13±0.01, 2.97±0.01 ,2.16±0.01 ,10.56±1.97, 24.97±2.4, respectively whilst in time intervals highest TPC for peel (118.66±8.9) mg/g was observed in 60 min followed by (102.33±7.6) mg/g at 90 min and (82.02±5.5) mg/g at 30 min respectively Whereas, the recorded TPC for pomace at 30, 60 and 90 minute were (112.73±9.1) mg/g has observed in 60 min followed by (97.21±7.9) mg/g at 90 min and (84.55±5.8) mg/g at 30 min respectively. Among the time intervals highest flavonoids contents of peel were at 60 min 52.3±1.9% followed by 52.51±1.7% at 90 min and minimum 50.72±1.4% at 30 min. The highest ABTS value was observed for peel content 248.33±5.6 Î¼g/ml in ethanol extract followed by methanolic extract 212.11±4.4 Î¼g/ml least in water extract 152.5±3.2 Î¼g/ml. The means reviewed FRAP activity highest value for ethanol in peel and pomace were (92.66±5.3 µg/ml Fe2+/g) & (82.47±4.2 µg/ml Fe2+/g) followed by methanol (86.33±4.1 µg/ml Fe2+/g) & (76.83±3.4 µg/ml Fe2+/g) and least in water (66.46±2.2 µg ml Fe2+/g) &(54.24±2.1 µg/ml Fe2+/g) respectively. The color acceptability varied significant effect between 7.49 to 7.55 in T0 to T3. Likewise, storage imparted more significant decline from 7.72 to 7.30 at 0th to 60th days, respectively. The flavor scores were 7.59, 7.41, 7.26 and 7.53 in T0, T1, T2 and T3 respectively. The overall acceptability of drink was significantly increase from initiation (0th) day to termination (60th) day as 7.68 to 6.9.